PENGARUH PERILAKU BELAJAR DAN KECERDASAN SPIRITUAL TERHADAP STRESS KULIAH MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PGRI SEMARANG - Mira Dwi Utami; Junita Widia Sukma; Rauly Sijabat (CV. ADIBA AISHA AMIRA, 2024)
The aim of this approach is to examine how learning behavior and spiritual intelligence can influence college stress levels for students at the Faculty of Economics and Business, PGRI University Semarang. The sample consisted of 25 respondents. Quantitative methods are used in this research with data collection techniques by distributing questionnaires and tested with the t test (multiple regression test) and the F test and with the coefficient of determination processed through SPSS 22. Based on the results of this research it is known that the two variables simultaneously significantly influence the variable college student stress. Therefore, the hypothesis of this study can be confirmed.